Increasing Student Learning Enthusiasm Through Multimedia-Based Learning - Abu Anwar; Samsi Hasan; Elin Haerani (STAI Hubbulwathan Duri, 2023)
A teaching device is a medium that can be used to convey material from a teacher to students. The delivery of material designed in the form of multimedia aims to make it easier for students to understand the material both in the form of desktop and web-based applications. A common problem faced by students is that there are still many who have not achieved satisfactory learning achievement. With the existing limitations, learning tools that support learning achievement are absolutely necessary. This research focuses on increasing student enthusiasm for learning in the Ulumul Quran course. Learning activities with multimedia-based applications aim to increase students' enthusiasm for learning, so that the material is absorbed more quickly and students are not bored. Initial observations included a literature review and interviews to identify class issues for lesson analysis and possible remedies. In developing the solution, the problem is identified based on course material, class schedule, student characteristics, class atmosphere, learning methods/approaches, process assessment, and learning outcomes. Then analyse data and demands and design a multimedia-based e-learning system. The conclusion of this study states that students are able to increase their enthusiasm for learning the subject 'Ulumul Qur'an. There is an increase in student enthusiasm for learning with multimedia-based learning. This can be seen in the average N-Gain value obtained 0.466. The significant value obtained from the calculation results is smaller than the significant level α = 0.05 (0.000 0.05) than H0, which states that there is no difference in the enthusiasm for learning of students who study.